Approaches to Contrastive Linguistics - Akhmanova, Olga.; Moscow State Univ. (U.S.S.R.), Faculty of Philology ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
Linguistics as a science has been concerned with comparison ever since its inception, the number and variety of approaches increasing steadily in the course of its development. Interest in linguistic comparison extends into the field of foreign language teaching. Linguists have attempted to solve the problem of methodology in contrastive linguistics by turning to the models of description that they favor, including: (1) contrastive transformational grammar, (2) the stratificational model, and (3) the sector analysis model. The present study is based on the categorical approach to contrastive linguistics, an approach whose underlying assumption is the existence of sets of categories, the most general being notional and conceptual ones, the most particular being morphological, grammatical and lexical ones. This study consists of a systematic contrastive analysis of the morphological categories of English verbs and verbs in four languages of the Soviet Union: Russian, Turkoman, Ossetic, and Georgian. (CLK)
ERIC Note: Best copy available.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Caucasian Languages; Contrastive Linguistics; Descriptive Linguistics; English; Form Classes (Languages); Grammar; Morphology (Languages); Ossetic; Russian; Structural Analysis; Verbs; Turkoman; Books